2008
DOI: 10.1124/mol.107.042010
|View full text |Cite
|
Sign up to set email alerts
|

TargetingMDR1Gene: Synthesis and Cellular Study of Modified Daunomycin-Triplex-Forming Oligonucleotide Conjugates Able to Inhibit Gene Expression in Resistant Cell Lines

Abstract: Reversal of the multidrug-resistant (MDR) phenotype is very important for chemotherapy success. In fact, the expression of the MDR1 gene-encoded P-glycoprotein (P-gp) actively expels antitumor agents such as daunomycin (DNM) out of the cells, resulting in drug resistance. We show that upon conjugation to triplex-forming oligonucleotides, it is possible to address DNM in resistant cells (MCF7-R and NIH-MDR-G185). The oligonucleotide moiety of the conjugate changes the cellular penetra-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…However, the strategy has never been applied to an endogenous target of therapeutic interest. Other studies have demonstrated the cellular efficacy of TFOs conjugated to daunomycin, a Top2 inhibitor, without demonstrating a mechanism via a Top2‐mediated DNA cleavage (4951). Thus, a clear demonstration of the mechanism of action in cells of the conjugates of TFOs attached to topoisomerase inhibitors was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strategy has never been applied to an endogenous target of therapeutic interest. Other studies have demonstrated the cellular efficacy of TFOs conjugated to daunomycin, a Top2 inhibitor, without demonstrating a mechanism via a Top2‐mediated DNA cleavage (4951). Thus, a clear demonstration of the mechanism of action in cells of the conjugates of TFOs attached to topoisomerase inhibitors was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, regulation of MDR-related gene expression is highly complex. For instance, such complexity is embodied in multiple transcription-regulatory elements in the 5' and 3' flanking sequences of the mdr-1 gene, and numerous protein factors involved in transcription-regulatory processes in a cell type-and stimulus-dependent manner [21] . The mechanism underlying the expression of MDR-related genes has not yet been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DNM–TFO conjugates showed sequence-specific inhibition of the targeted gene, without however an effect of the anti-cancer activity of DNM. We recently demonstrated that conjugation of DNM to TFOs allowed to inhibit transcription of the target gene ( MDR 1) by a specific role of the DNM moiety (178). Furthermore, if these conjugates are employed in DNM-resistant cell lines, the uptake of DNM itself is permitted by the presence of the oligonucleotide, thus showing a mutual action of the partners of these conjugates, the DNM and the TFO.…”
Section: In Vitro Applications Of Tfos As Gene Modulatorsmentioning
confidence: 99%